Epidemiology and risk factors of fungal pathogens in sepsis: a prospective nationwide multicenter cohort study - Jeong Eun Lee; Da Hyun Kang; Hyekyeong Ju; Dong Kyu Oh; Su Yeon Lee; Mi Hyeon Park; Chae-Man Lim; Song I Lee; On behalf of the Korean sepsis Alliance (KSA) investigators (BMC Infectious Diseases)
Abstract Background The incidence of sepsis with identified fungal pathogens is increasing and is associated with higher morbidity and mortality. Co-infection with fungal infections in COVID-19 patients is attracting clinical attention. This study examines the epidemiology, risk factors, and outcomes among sepsis patients with identified fungal pathogens. Methods We conducted a nationwide cohort study of adult patients with sepsis from the Korean Sepsis Alliance Database in South Korea between September 2019 and December 2021. We identified 407 patients with documented fungal pathogens, categorized according to the presence of hemato-oncologic malignancies. Results Of the 11,981 patients with sepsis, fungal pathogens were identified in 3.4% of cases. Among these patients, 38.3% had co-existing hematologic or solid organ cancer. Older age, higher clinical frailty scale scores, and underlying conditions, such as chronic kidney disease, cerebrovascular disease, and dementia, were more prevalent in patients without hemato-oncologic malignancies. The most common fungal pathogens were Candida albicans (47.9%), Candida glabrata (20.6%), and Candida tropicalis (13.5%). Only 6.6% of the patients with confirmed fungal pathogens received antifungal treatment. The presence of hemato-oncologic malignancies did not significantly affect patient outcomes. Factors associated with the presence of identified fungal pathogens included chronic kidney disease (Odds ratio [OR] 1.662; 95% confidence interval [CI] 1.216–2.273; p = 0.001), connective tissue disease (OR 1.885; 95% CI 1.058–3.358; p = 0.032), immunocompromised status (OR 2.284; 95% CI 2.186–3.753; p = 0.001), and invasive mechanical ventilation (OR 2.864; 95% CI 2.186–3.753; p < 0.001). Conclusions Sepsis identified fungal pathogen are associated with chronic kidney disease, immunocompromised status and other risk factors, demonstrating the need for early detection, targeted management and improved antifungal strategies to improve patient outcomes.